Endocrine Factors Modulating Immune Responses in Pregnancy - Schumacher, Anne; Costa, Serban-Dan; Zenclussen, Ana Claudia (Frontiers in Immunology, 2014)
How the semi-allogeneic fetus is tolerated by the maternal immune system remains a fascinating phenomenon. Despite extensive research activity in this field the mechanisms underlying fetal tolerance are still not well understood. However, there are growing evidences that immune-immune interactions as well as immune-endocrine interactions build up a complex network of immune regulation that ensures fetal survival within the maternal uterus. In the present review, we aim to summarize emerging research data from our and other laboratories on immune modulating properties of pregnancy hormones with a special focus on progesterone, estradiol and human Chorionic Gonadotropin. These pregnancy hormones are critically involved in the successful establishment, maintenance and termination of pregnancy. They suppress detrimental maternal alloresponses while promoting tolerance pathways. This includes the reduction of the antigen-presenting capacity of dendritic cells, monocytes and macrophages as well as the blockage of natural killer cells, T and B cells. Pregnancy hormones also support the proliferation of pregnancy supporting uterine killer cells, retain tolerogenic dendritic cells and efficiently induce regulatory T cells. Furthermore, they are involved in the recruitment of mast cells and regulatory T cells into the fetal-maternal interface contributing to a local accumulation of pregnancy-protective cells. These findings highlight the importance of endocrine factors for the tolerance induction during pregnancy and encourage further research in the field.